Fracture behavior of cancellous bone and cancellous bone-PMMA bone cement interface: An experimental study using an integrated methodology (wedge splitting test and Heaviside-based digital image correlation). (October 2021) - Bokam, P.; Germaneau, A.; Breque, C.; Rigoard, P.; Vendeuvre, T.; Valle, V.
Abstract: Minimally invasive methods, such as balloon kyphoplasty (BKP) and percutaneous sacroplasty (PS), which are now widely used for the surgical treatment of compression fractures, involve injection of a bolus of poly (methyl methacrylate) bone cement (hereafter, "bone cement") into the fractured tissue. Many of the common complications following these surgeries, such as cement leakage and adjacent-level fractures (in the case of BKP), have been postulated to be related to the quality of the cancellous bone–bone cement interface, which, in turn, is a function of its fracture resistance. It is common to use bovine cancellous bone or polyurethane foam (PF) as a substitute for human cancellous bone in biomechanical studies of these surgical methods. The literature is lacking in studies of determination of fracture properties of human cancellous bone–bone cement interface, bovine cancellous bone–bone cement interface, and PF–bone cement interface. In the present work, an integrated methodology (combination of wedge splitting test and Heaviside-based digital image correlation) was used to make these determinations as well as those for the bone cement, bones and the PF alone. The fracture properties determined were maximum fracture load ( F max ), fracture toughness (K c ), and specific fracture energy (G f ). For example, G f values for human cancellous bone and human cancellous bone–bone interface were 0.48±0.14 N/mm and 0.38±0.05 N/mm, respectively, whereas in the case of bovine cancellous bone and bovine cancellous bone–bone cement interface, they were 1.08±0.11 N/mm and 0.22±0.05 N/mm, respectively, and for PF (Grades 12.5 and 15.0) and PF–bone cement interface, they were 0.81±0.12 and 0.55±0.06 N/mm, respectively. The same trends were seen in the  F max and K c results. These results suggest that it may not be justified to use either bovine cancellous bone or either of the PF grades as a substitute for human cadaveric cancellous bone in biomechanical studies of BKP, PS, and similar surgical methods.